2009
DOI: 10.1002/lary.20653
|View full text |Cite
|
Sign up to set email alerts
|

Long‐term outcomes from the English national comparative audit of surgery for nasal polyposis and chronic rhinosinusitis

Abstract: We have shown sinonasal surgery to be safe and effective in reducing the symptoms associated with CRS over a 5-year period. The reduction in symptoms is large, with no significant decline in symptomatic improvement from 12 to 60 months postsurgery. However, revision surgery rates approach 20% over this time, and patients should be counseled accordingly prior to surgery.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

20
256
1
17

Year Published

2012
2012
2021
2021

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 258 publications
(294 citation statements)
references
References 13 publications
20
256
1
17
Order By: Relevance
“…Inflammation and CT scores are higher in CRSwNP (in patients in cluster 1) which does not seem to result in worse outcomes compared to male CRSsNP patients, and they are better than those of CRSsNP female patients. This confirms previous findings that CRSwNP patients demonstrate more satisfaction with surgical outcomes and suggests that comparison between mixed groups of CRS patients with and without nasal polyps is unhelpful [12]. …”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…Inflammation and CT scores are higher in CRSwNP (in patients in cluster 1) which does not seem to result in worse outcomes compared to male CRSsNP patients, and they are better than those of CRSsNP female patients. This confirms previous findings that CRSwNP patients demonstrate more satisfaction with surgical outcomes and suggests that comparison between mixed groups of CRS patients with and without nasal polyps is unhelpful [12]. …”
Section: Discussionsupporting
confidence: 79%
“…It has been suggested that, besides differences in symptom patterns, major phenotypes differ in the response to surgical or combined (surgical and drug) treatment [12]. Early recognition of patients who are refractory to long-term medical and surgical treatment may prevent repetitive unnecessary sinus surgery and potential complications of such procedures.…”
Section: Introductionmentioning
confidence: 99%
“…As this study design set out to be representative of the daily clinical practice, it did not enable us to add a 1-year clinical followup. However, previous long-term studies have documented that the effects of ESS measured after 3-12 months, are likely to be sustained over a 5-year period [28,29].…”
Section: Strengths and Weaknessmentioning
confidence: 97%
“…Usually the oedema phase takes approximately 30 days, and after three months the healing process is complete [20]. Baumann et al [21] and Hopkins et al [22] determined there was no difference or significant outcome of SNOT-20 GAV between the three month and the one year data collection results and the five year results. Not all patients in this study had preoperative medication for bronchial asthma or COPD.…”
Section: Discussionmentioning
confidence: 99%